Proceedings of the meeting of ministers (27-30 November 1961) - General Agreement on Tariffs and Trade (Organization). (Geneva : [Contracting Parties to the] General Agreement on Tariffs and Trade, 1962)
This book is a reproduction of all the statements made by Ministers and ministerial representatives, as well as the conclusions adopted at the ministerial meeting reaffirming at the political level, the confidence of governments in the General Agreement on Tariffs and Trade, and their determination to increase its effective application
At head of title: General agreement on tariffs and trade.
osc 19/11/2018
Loans
Keywords: Tariff